2020
DOI: 10.1097/jcma.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Initiating palliative care consultation for acute critically ill patients in the emergency department intensive care unit

Abstract: Background: Little is known about the characteristics of patients needing palliative care consultation in the emergency department (ED). This study aimed to investigate the impacts of initiating screening in acute critically ill patients needing palliative care on mortality, health care resources, and end-of-life (EOL) care in the intensive care unit in ED (EICU). Methods: We conducted an analysis study in Taipei Veterans General Hospital. From February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In some studies performed on palliative care patients, it has been reported that the duration of stay in emergency services varies between 3.5-16 hours. 18,[20][21][22] In our study, it was determined that the mean duration of stay in EDs was 9.97 hours.…”
Section: Discussionmentioning
confidence: 77%
“…In some studies performed on palliative care patients, it has been reported that the duration of stay in emergency services varies between 3.5-16 hours. 18,[20][21][22] In our study, it was determined that the mean duration of stay in EDs was 9.97 hours.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies suggest that functional status is also a strong predictor for mortality rate [ 46 , 47 ]. Functional status has been integrated as a part of the screening criteria of the palliative care tool we used in this study [ 20 ], which allowed us to limit all patients’ functional status to a certain degree. However, future studies may consider functional status as another independent predictor when assessing palliative care needs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were categorized into three end-of-life trajectories (terminal cancer, organ failure, and frailty) according to their main illness using a screening tool established beforehand [ 20 ]. In the present study, we used the criteria defined by the screening tool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization criteria were formulated by palliative care (PC) and hospice specialists and adopted to identify patients at high risk of poor clinical outcomes as their care commonly involves prolonged use of advanced medical resources or technologies [10]. Two trained authors entered the abstracted data for study analyses.…”
Section: Palliative Care Assessment and Data Collectionmentioning
confidence: 99%